(untitled) (Research, Society and Development, 2021)
This study aimed to seek the main themes related to studies on the principle of comprehensiveness in Primary Health Care (PHC), in an approach to oral health. This is an integrative literature review carried out between November and December 2020, through the Virtual Health Library, in the databases: Latin American Literature in Health Sciences (LILACS), Medical Literature Analyzes and Retrieval System Online (MEDLINE) and Brazilian Dentistry Bibliography (BBO). The final sample consisted of 12 articles, after the search and selection process. Oral health care in primary health care takes place mainly through curative procedures. The main collective procedures are: lecture, health education activity, supervised brushing, topical application of fluoride, oral examination. The studies in this review showed that access to oral health actions is mainly aimed at the complaints of patients, with procedures, in most cases, curative and with low resolution.